Use of spoligotyping and large sequence polymorphisms to study the population structure of the Mycobacterium tuberculosis complex in a cohort study of consecutive smear-positive tuberculosis cases in The Gambia. - (:unkn) unknown (My University, 2009)
Mycobacterium africanum, first described in Senegal in 1968, causes up to half of the smear-positive pulmonary tuberculosis cases in West Africa, but it has not been found in other geographical areas except among recent West African migrants. The reasons for the geographic restriction of M. africanum are unknown. We used molecular tools to determine the population structure of the Mycobacterium tuberculosis complex in a cohort study of consecutive smear-positive tuberculosis cases in The Gambia. We collected and genotyped 386 clinical isolates using spoligotype analysis and PCRs for large sequence polymorphisms (LSPs) and compared the genotype patterns to the patterns in an international database. The results of spoligotyping and LSP analysis for the study population were also compared to determine the correlation between them. The main lineages within the Mycobacterium tuberculosis complex identified in The Gambia included M. africanum type I (38.4%), characterized by an LSP in region of difference 702 (RD702; West African type 2). Among the M. tuberculosis sensu stricto isolates, lineages characterized by RD182 and by RD174 were the most common. We also detected a gradient in the prevalence of M. africanum that extended from neighboring Guinea-Bissau. The genotypic diversity of the spoligotype patterns was greater among the isolates of M. africanum than among the isolates of M. tuberculosis. We postulate that M. africanum became endemic in West Africa first, before the introduction of different lineages within M. tuberculosis sensu stricto.
Keywords: African Research